Measuring Dynamic Effects of Remittances on Poverty and Inequality with Evidence from Kosovo. Issue 4 (3rd July 2020) - Arapi-Gjini, Arjola; Möllers, Judith; Herzfeld, Thomas
ABSTRACT: This paper investigates dynamic effects of remittances on households' poverty and income distribution. Using state-of-the-art matching techniques, we measure impacts based on counterfactual scenarios, and make a step forward by applying for the first time a dose-response function approach to assess poverty effects due to variations in the time-length of receiving remittances. Our results suggest that remittances alleviate both absolute and relative poverty levels and lead to a marginal increase in inequality in the case of Kosovo. We further demonstrate that – although poverty reduction effects are stronger in the short-run – remittances have a positive poverty reduction effect over time. These findings have important welfare policy implications for low- and middle income economies with a high dependency on remittances.